THE STUDENTS’ MOTIVATION IN STUDYING ENGLISH AT SMPN 5 LEMBANG PINRANG - Fitriani, Indah; Kalsum, Kalsum; Sardi, Ahmed (elstic : english language linguistics culture, 2024)
Motivation is one of the factors to support English learning process. Motivation in learning can be devided into two categories intrinsic and extrinsic motivation. Where motivation is one of the most significal things in learning process. Without motivation, the purposes of learning are tough to be achieved. When learners have itu in learning process, they win more understand with the materials, especially English. Eventually, the purpose of this research was to find out the kind of motivation is dominant in studying English at SMPN 5 Lembang. The research design of this study is descriptive quantitative by using survey method. The population of this research was all of students’ SMPN 5 Lembang, meanwhile the sample of this research was taken 39. After the research had been conducted, it was found that intrinsic motivation has a score of 48% and extrinsic motivation has a score of 52%. After it was found about the score of intrinsic and extrinsic motivation. From the calculated of the students’ score, the kind of motivation that is dominant in studying English is Extrinsic motivation.